2020
DOI: 10.1371/journal.pone.0230894
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence: A key correlate of women’s physical and mental health in informal settlements in Nairobi, Kenya

Abstract: Globally, one billion people live in informal settlements, and that number is expected to triple by 2050. Studies suggests that health in informal settlements is a serious and growing concern, yet there is a paucity of research focused on health outcomes and the correlates of health in these settlements. Studies cite individual, environmental and social correlates to health in informal settlements, but they often lack empirical evidence. In particular, research suggests that high rates of violence against wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 67 publications
2
39
1
Order By: Relevance
“…Our extensive formative phase revealed high feasibility and acceptability of community-partnered technologybased safety planning intervention within Nairobi's informal settlements, where the high prevalence and health impact of IPV has garnered calls for prevention and response [13]. Moreover it generated necessary refinements to ensure successful implementation that builds on the strengths of this community.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our extensive formative phase revealed high feasibility and acceptability of community-partnered technologybased safety planning intervention within Nairobi's informal settlements, where the high prevalence and health impact of IPV has garnered calls for prevention and response [13]. Moreover it generated necessary refinements to ensure successful implementation that builds on the strengths of this community.…”
Section: Discussionmentioning
confidence: 97%
“…In Kenya, national data from 2014 indicates that 39% percent of ever-married women age 15-49 have ever experienced spousal physical or sexual violence, relative to 9% of ever-married men in the same age group [12]. The prevalence of IPV is even higher in Nairobi's informal settlements, and confers profound consequences to physical, sexual and mental health [13]. Social norms create a culture of IPV tolerance that challenges women's ability to seek help or identify their experiences as abuse [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to a cross-sectional study with urban refugee youth in Kampala's informal settlements, that used different scoring methods and found two-thirds reported any depression symptoms, we found that violence exposure, food insecurity, and lower social support were associated with depression [20] . Violence exposure is a stressor associated with a sequalae of poor health outcomes, including mental health disorders, in internally displaced communities in Northern Uganda [41] , rural refugee settlements in Uganda and Rwanda [42] , with adolescents in Kampala [40] , and in urban informal settlements in Kenya [43] and South Africa [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although IPV is not a new phenomenon for sex workers (see, e.g. for Pack et al, 2014;Winter et al, 2020), and Kenya possesses well-established networks of NGOs that specifically respond to gender-based violence, including IPV (Ondicho, 2018), the state has closed many of the faith-based rescue centres, leading excess case-management burden to fall on sex worker-led organisations. Such organisations do not possess the specialized training and resources to effectively respond to the increased urgency of members around IPV.…”
Section: Health Services Challenges and Responsesmentioning
confidence: 99%